Respuesta :

B

note that (f + g)(x) = f(x) + g(x)

f(x) + g(x) = -4x² - 6x - 1 - x² - 5x + 3 ( collect like terms )

               = - 5x² - 11x + 2


Answer:

The correct option is B.

Step-by-step explanation:

The given functions are

[tex]f(x)=-4x^2-6x-1[/tex]

[tex]g(x)=-x^2-5x+3[/tex]

Using the p addition property of functions (f + g)(x) can be written as

[tex](f+g)(x)=f(x)+g(x)[/tex]

Substitute the values of each function in the above equation.

[tex](f+g)(x)=-4x^2-6x-1-x^2-5x+3[/tex]

Combine like terms.

[tex](f+g)(x)=(-4x^2-x^2)+(-6x-5x)+(-1+2)[/tex]

[tex](f+g)(x)=-5x^2-11x+2[/tex]

Therefore the correct option is B.